Analogical Arguments in Persuasive and Deliberative Contexts - Walton, Douglas; Hyra, Curtis (Informal Logic)

(untitled) (Informal Logic, 2018)
This paper uses argumentation tools such as argument diagrams and argumentation schemes to analyze four examples of argument from analogy, and argues that to proceed from there to evaluating these arguments, features of the context of dialogue need to be taken into account. The evidence drawn from these examples is taken to support a pragmatic approach to studying argument from analogy, meaning that identifying the logical form of the argument by building an argument diagram of the premises and conclusion is not by itself sufficient for argument evaluation. To get further, it is argued, the argument evaluator needs to take into account how this particular argument was used in context to support a conversational goal.